THE WAYS TO PROVIDE SERVICE IN THE TIME OF TECHNOLOGICAL INTENSIFICATION: ANEW CONCEPT OF E-PROFESSIONS IN THE PROCESS OF CREATING ARCHITECTURE OF AN ONLINE COURSE (Research Bulletins of the Faculty of Economic Sciences, 2021)
The author takes an attempt to look on technological and information revolution in context of creating a new professional value on the labour market. As shown the differ-ence between generations has an influence on the performance of the actual work be-cause of personal aspirations and needs. The main goal of this article is to outline a new dehumanized quality of workand systematized new occupations concentrated around the creation of an educational platform. It may constitute added value to the polishlabour market.
Keywords: new occupations, e-professions, professionaltransformation,dehumanisationof work,creating an online course